Pathogenesis and therapeutic implications of EBV-associated epithelial cancers - Low, Yi Hua; Loh, Celestine Jia Ling; Peh, Daniel Yang Yao; Chu, Axel Jun Ming; Han, Shuting; Toh, Han Chong (Frontiers in Oncology, 2023)
Epstein-Barr virus (EBV), one of the most common human viruses, has been associated with both lymphoid and epithelial cancers. Undifferentiated nasopharyngeal carcinoma (NPC), EBV associated gastric cancer (EBVaGC) and lymphoepithelioma-like carcinoma (LELC) are amongst the few common epithelial cancers that EBV has been associated with. The pathogenesis of EBV-associated NPC has been well described, however, the same cannot be said for primary pulmonary LELC (PPLELC) owing to the rarity of the cancer. In this review, we outline the pathogenesis of EBV-associated NPC and EBVaGCs and their recent advances. By drawing on similarities between NPC and PPLELC, we then also postulated the pathogenesis of PPLELC. A deeper understanding about the pathogenesis of EBV enables us to postulate the pathogenesis of other EBV associated cancers such as PPLELC.